Rapid and high biodegradation of phenols catalyzed by Candida tropicalis NCIM 3556 cells - Varma, Rita J.; Gaikwad, Bhaskar G. (Enzyme and Microbial Technology, 2008)
Cells of 19 yeast cultures, belonging to genus Candida were screened for biodegradation of phenol. The cultures procured from NCIM culture collection and were selected so as to contain a representative of varied strains of the species. These were grown in MGYP3 medium and tested for biodegradation of phenol. C. tropicalis (CT) nos. 3118, 3556 and C. lipolytica 3472 effectively degraded >90% 2 g l(-1) phenol. The C. tropicalis 3556 strain was selected for further studies as it metabolized >95% phenol in just 16 h as compared to the other two which took 48 h. The maximum substrate concentration that could be completely degraded was 2 g l(-1). A study of induction, of different concentration of phenol in the growth medium showed that toxicity to cell growth increased with increasing phenol levels in growth media. Biodegradation of phenol derivatives - o-cresol, m-cresol. 2,6-dimethyl phenol, alpha-naphthol, o-chlorophenol and p-nitrophenol, by the selected three strains indicated that the specificity of each culture varied for different substrate. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Biodegradation; Candida lipolytica; Candida tropicalis; phenol; Phenol derivatives

Spectrophotometric method for estimation of aliphatic primary amines in biological samples - Varma, Rita J.; Gaikwad, Bhaskar G. (World Journal of Microbiology & Biotechnology, 2008)
A method based on Rimini test for aliphatic amines was studied and developed for quantitative estimation of aliphatic primary amines. The method involves action of the amine with acetone to form schiff base which complexes with sodium nitroprusside to give violet colour. The absorption maximum in the visible range of the spectrum, for the reaction mixture was found to be 550 nm. The pH (8-11) and reaction time scan for the assay were optimized. A linear relation of concentration (0.2-3 mg/mL) of amine against absorbance at 550 nm was established. Interference due to other reaction components was negligible (+/- 0.02 mg/mL) as compared to the sample in buffer. 1,3-dimethyl butylamine was used as the model amine and the method was applied to other amines; it was observed that when electron-withdrawing substituents are present in the molecule the reaction is retarded, as the incubation time was longer. This method is useful for estimation of aliphatic primary amine in biological samples.
Keywords: determination; estimation; primary aliphatic amines; Schiffs base; sodium nitroprusside; spectrophotometric